ANALISA KONTRAK PROYEK KONSTRUKSI DI INDONESIA - Simanjuntak, Johan Oberlyn; Bartholomeus; Simanjuntak, Salomo; Lumbangaol, Partahi; Astri Agnes (Jurnal Visi Eksakta, 2021)
The contract is a very importand document in the project. Contract are seen as laws that must be obeyed, govern and control the rights and obligations between service users and service providers in the project. In world of construction in Indonesia, the standard used for contract documents must be based on Law No.2 of 2017 on construction services as a guide and guidance in constructions activities in Indonesia. In the international world, FIDIC documents has long been recognized, which is a contractual rule that has been used by many countries. FIDIC has also been widely adapted to government and private projects in Indonesia. The first analysis is to identify the contract documents used in several project in North Sumatera region. This analysis shows that the FIDIC red book document is the most suitable document to be used in several project in North Sumatera. The second analysis is comparing the FIDIC document and the analysis shows that the contract document that best matches the points in the questionnaired is Law No. 2 of 2017 on construction services. From the analysis of the previous discussion a conclusion was drawn regarding the philosophy of the work contract discussed was the type of unit price contract based on.